A pan-cancer analysis of the oncogenic function of HMGB1 in human tumors - Hui-min Yang; Xiang-ning Zhao; Xiao-ling Li; Xi Wang; Yu Pu; Dong-kai Wei; Zhe Li (Biochemistry and Biophysics Reports)
Background: Although high mobility group box protein 1 (HMGB1) has been researched in relation to cancer in many investigations, a thorough investigation of its role in pan-cancer has yet to be conducted. With the objective of bridging this gap, we delved into the functions of HMGB1 in various tumors. Methods: This investigation employed The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) databases to examine HMGB1 gene expression differences and correlation with survival across various human tumors. Then, genetic alterations of HMGB1 were analyzed by tool cBioPortal, and immune cell infiltration was assessed. Finally, we gathered clinial samples from 95 patients with various types of solid tumor and performed somatic mutation analysis using panel sequencing. This further highlighted the role of HMGB1 in different solid tumors. Results: There was a notable elevation of HMGB1 gene expression in tumor tissues as opposed to non-cancerous tissues across the bulk of tumor types. Elevated HMGB1 gene expression had a connection with shorter overall survival, progression-free survival, and disease-free survival in specific tumor types. Genetic alterations of HMGB1 suggested that the amplifications and mutations of HMGB1 may impact the prognosis of breast cancer (BRCA) and liver hepatocellular carcinoma (LIHC). Both BRCA and mesothelioma (MESO) displayed a connection between the infiltration of cancer-associated fibroblasts (CAFs) and HMGB1 gene expression. Moreover, HMGB1 co-expression analysis revealed its association with genes involved in RNA splicing, mRNA processing, and modulation of mRNA metabolic processes. Additionally, a pathway analysis by use of the Kyoto Encyclopedia of Genes and Genomes (KEGG) unveiled that HMGB1 was implicated in the pathogenic mechanisms of ''Hepatitis B,'' ''Viral Carcinogenesis,'' and ''Hepatocellular Carcinoma.'' Based on somatic mutation analysis of 95 patients with different solid tumors, we found that the frequency of HMGB1 mutations was higher in Liver cancer patients compared to other solid tumors. This finding is consistent with our in-silico study results. Additionally, we discovered that the frequency of HMGB1 mutations ranked among the top 20 mutated genes in the 95 patients’ data, indicating that HMGB1 plays an important role in the development and prognosis of various solid tumors. Conclusion: This pan-cancer study of HMGB1 underscores its potential as a signature marker and target for the management of various tumor types.